Identifikasi Penyebab Keterlambatan Penyediaan Dokumen Rekam Medis Rawat Jalan di Rumah Sakit Husada Utama Surabaya Tahun 2020 - Astrid Kartika Dewi Aprilia; Ida Nurmawati; Rossalina Adi Wijayanti (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Fast and precise services are the desire of consumers. The speed of document provision of medical records to the PDS can be an indicator in measuring satisfaction. Based on the SPM of the hospital when providing outpatient medical records is â‰¤ 10 minutes. Husada Utama Surabaya Hospital has implemented medical records management, but there are problems in the implementation, in the provision of medical record documents less than the maximum and delayed. The aim of this research is to determine the factors causing delays in the provision of patient medical record documents in outpatient services based on 7M (man, money, method, material, machine, motivation, and media). This type of research is qualitative. Data collection used observation sheets and interview guidelines to 4 respondents. The results showed that the education, knowledge, and training of employee about the science of medical records is still lacking, the budget was managed by the financial management and there were no details for the needs of the medical record unit, there is no SOP about the provision of outpatient medical record documents, the medical record file is only a thin sheet of HVS paper, the folder used is easily damaged, outpatient medical records employee never get a reward from the leadership, room and rack filling cannot store medical records medical records properly. In conclusion, the factors that caused the delay in providing medical record documents are man, money, method, material, motivation, and media. The results of this study can be an evaluation material for Husada Utama Hospital to improve the service provision of medical records for outpatients.